Literature Review: Natural Anthelmintic from Moringa Leaves (Moringa oleifera) for Controlling Haemonchus contortus in Goats - Wulandari, Aprilia Rizki; Dewatisari, Whika Febria (Jurnal Biologi Tropis, 2025)
Haemonchus contortus remains one of the most pathogenic gastrointestinal nematodes in goats, causing substantial productivity losses in small ruminant farming. The increasing resistance and residue concerns associated with synthetic anthelmintics highlight the need for safer, plant-based alternatives. This study aims to review the potential of Moringa oleifera leaves as a natural anthelmintic for controlling Haemonchus contortus infections in goats. A non-systematic literature review was conducted by screening scientific articles published between 2019 and 2024 through Google Scholar using keywords related to alternative natural anthelmintics, control of goat parasites, Haemonchus contortus infection, Moringa oleifera, and plant phytochemical compounds. Relevant in vitro and in vivo studies were analyzed descriptively to evaluate the plant’s phytochemical profile, mechanisms of action, and effectiveness. Findings indicate that Moringa oleifera leaves contain tannins, saponins, flavonoids, alkaloids, and terpenoids that inhibit egg hatching, disrupt larval development, and impair adult worm survival. In vitro studies consistently demonstrate high ovicidal, larvicidal, and vermicidal activity, with inhibition rates comparable to albendazole at higher concentrations. In vivo results also show significant reductions in fecal egg counts (FEC), particularly at doses of 200–400 mg/kg body weight, without reported adverse effects. These outcomes underline the effectiveness and safety of Moringa oleifera leaves as a promising natural anthelmintic. In conclusion, Moringa oleifera represents a viable, environmentally friendly option for integrated parasite control in goats, particularly for reducing infections caused by Haemonchus contortus. Further standardized dosing studies and long-term evaluations are recommended to optimize its practical application in small ruminant health management.